Trade booms, trade busts, and trade costs - David S. Jacks; Christopher M. Meissner; Dennis Novy (Center for Economic Studies and ifo Institute (CESifo), 2009)
What has driven trade booms and trade busts in the past and present? We derive a micro-founded measure of trade frictions from leading trade theories and use it to gauge the importance of bilateral trade costs in determining international trade flows. We construct a new balanced sample of bilateral trade flows for 130 country pairs across the Americas, Asia, Europe, and Oceania for the period from 1870 to 2000 and demonstrate an overriding role for declining trade costs in the pre-World War I trade boom. In contrast, for the post-World War II trade boom we identify changes in output as the dominant force. Finally, the entirety of the interwar trade bust is explained by increases in trade costs.
Keywords: F10; F15; N10; N70; 330; Außenwirtschaft; Internationale Wirtschaftsbeziehungen; Transaktionskosten; Außenhandelsgeschichte; Welt